Multiphoton Excitation: Confinement of Perovskite‐QDs within a Single MOF Crystal for Significantly Enhanced Multiphoton Excited Luminescence (Adv. Mater. 6/2019). Issue 6 (8th February 2019) - He, Huajun; Cui, Yuanjing; Li, Bin; Wang, Bo; Jin, Chuanhong; Yu, Jiancan; Yao, Lijia; Yang, Yu; Chen, Banglin; Qian, Guodong
Abstract : The confinement effect and protection of a metal–organic framework (MOF) not only significantly diminish the aggregation‐caused quenching effect and provide effective surface passivation of perovskite QDs, but also greatly reduce the contact of perovskite QDs with the external "bad" atmosphere, liberating excellent luminescence and nonlinear optical properties of perovskite QDs from the solution system to the solid single‐crystal system, as described by Banglin Chen, Guodong Qian, and co‐workers in article number1806897 .